2021
DOI: 10.1111/psyp.13800
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac, vasomotor, and myocardial branches of the baroreflex in fibromyalgia: Associations with pain, affective impairments, sleep problems, and fatigue

Abstract: This study investigated the cardiac, vasomotor, and myocardial branches of the baroreflex in fibromyalgia using the spontaneous sequence method. Systolic blood pressure (SBP), interbeat interval (IBI), stroke volume (SV), pre‐ejection period (PEP), and total peripheral resistance (TPR) were continuously recorded in 40 fibromyalgia patients and 30 healthy individuals during a cold pressor test and a mental arithmetic task. Sequences of covariation between SBP and IBI (cardiac branch), SV and PEP (myocardial bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 98 publications
(184 reference statements)
2
17
0
Order By: Relevance
“…During resting conditions and low psychophysiological activation, IBI almost entirely depends on parasympathetic activity (37), such that the subgroup difference in this parameter also confirms lower parasympathetic influences in individuals with depression. As the main mechanism of short-term BP regulation, the cardiac baroreflex responds to BP fluctuations with compensatory adjustments of HR, myocardial contractility, and vasomotor tone (17); BRS, as assessed in this study, reflects the strength of the compensatory HR response transmitted by vagal inputs on the sinus node. Therefore, the BRS reduction in FM patients with depressive disorders but not in those without depressive disorders also supports the conclusion that depressive disorders are relevant to the reduced parasympathetic control seen in individuals with FM (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During resting conditions and low psychophysiological activation, IBI almost entirely depends on parasympathetic activity (37), such that the subgroup difference in this parameter also confirms lower parasympathetic influences in individuals with depression. As the main mechanism of short-term BP regulation, the cardiac baroreflex responds to BP fluctuations with compensatory adjustments of HR, myocardial contractility, and vasomotor tone (17); BRS, as assessed in this study, reflects the strength of the compensatory HR response transmitted by vagal inputs on the sinus node. Therefore, the BRS reduction in FM patients with depressive disorders but not in those without depressive disorders also supports the conclusion that depressive disorders are relevant to the reduced parasympathetic control seen in individuals with FM (58).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies pointed toward blunted cardiovascular reactivity to physical and mental stressors in individuals with FM, reflected in diminished responses in IBI, HRV, blood pressure (BP), BRS, and indicators of sympathetic cardiac control, like the preejection period (PEP) and stroke volume (SV) (12)(13)(14)(17)(18)(19)(20). With respect to FM pathology, cardiovascular dysregulations were considered to be implicated in hyperalgesia, as well as other characteristic symptoms like affective impairments, sleep problems, and fatigue (13,14,17,21).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that an association between HRV and disability has been reported in other pain conditions [ 67 , 68 ], this assessment would have helped to better describe our sample and to control its impact on the treatment outcome results. Finally, the interpretation of LF and the LF/HF ratio are discussed in the scientific literature [ 16 , 69 , 70 ]. However, this is not the case for HF, whose interpretation is easier.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Furlan, et al 2005 [ 17 ], showed, with microneurography—the reference method for sympathetic activity in humans—that FM patients exhibited higher values of muscle sympathetic nerve activity (MSNA) associated with normalized LF, LF/HF and lower HF in comparison with controls. This autonomic imbalance was found at rest, but many studies showed reduced sympathetic reactivity to stress in this clinical population [ 7 , 8 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation